Impact of Preoperative Echocardiograms on In-Hospital Outcomes of Patients Undergoing Surgical Hip Fracture Repair and Their Clinical Appropriateness. Issue 5 (May 2023) - Tuli, Aakash; Gadodia, Ritika; Meda, Namratha; Arar, Tareq; Gautam, Monika; Zaghlol, Louay; Rasheed, Ahmed D.; Kallur, Akhil; Agrawal, Rajeev; Govindu, Rukma; Pristoop, Raphael; Chai, Christina; et al.
Abstract : The utility of preoperative transthoracic echocardiogram (TTE) before hip fracture repair remains controversial. This is a retrospective chart review study of adult patients admitted with hip fractures from multiple sites, including tertiary and community hospitals, with teaching and nonteaching services. The study compared the length of stay, time to surgery, in-hospital mortality, and postoperative complications between TTE and non-TTE groups. TTE patients were risk stratified using the Revised Cardiac Risk Index to compare TTE indications according to contemporary guidelines. Abstract: Objectives: Preoperative transthoracic echocardiograms (TTE) before hip fracture repairs are controversial. This study aimed to quantify the frequency of ordering TTE, the appropriateness of testing based on current guidelines, and the impact of TTE on in-hospital morbidity and mortality outcomes. Methods: This retrospective chart review of adult patients admitted with hip fracture compared the length of stay (LOS), time to surgery, in-hospital mortality, and postoperative complications between TTE and non-TTE groups. TTE patients were risk stratified using the Revised Cardiac Risk Index (RCRI) to compare TTE indication according to current guidelines. Results: Of the 490 patients included in this study, 15% received preoperative TTE. The median LOS of the TTE and non-TTE groups was 7.0 and 5.0 d, respectively, whereas the median time to surgery was 34 and 14 h, respectively. The odds of in-hospital mortality remained significantly higher in the TTE group after adjusting for RCRI but not when adjusted for the Charlson Comorbidity Index. Significantly more patients in the TTE groups had postoperative heart failure and up triage in the intensive care unit. Furthermore, 48% of patients with an RCRI score of 0 received preoperative TTE, with cardiac history as the most typical indication. TTE changed perioperative management in 9% of patients. Conclusions: Patients subjected to TTE before hip fracture surgery had a longer LOS and time to surgery, with higher mortality and intensive care unit up triage rates. TTE evaluations were typically conducted for inappropriate indications, which rarely made meaningful changes to patient management.